鉱石・炭材の配置と反応性が高炉融着帯反応・通気特性に及ぼす影響 - 砂原, 公平; 宇治澤, 優; 村上, 太一; 葛西, 栄輝 (鉄と鋼, 2016)
The placement control of iron ore and carbon in the blast furnace is one of the effective methods to improve the reaction efficiency and permeability. To clarify the increasing the reaction rate and decreasing the high temperature gas flow resistance, softening-melting test which changed the placement conditions in the packed bed of carbon composite iron-ore and the mixture of coke and ore was carried out. The effect of placement (i.e. packing structure) and reactivity of iron-ore and carbon on soften-melting properties at lower part of blast furnace were evaluated, and following results were obtained.1) The starting temperature of solution loss reaction decreased using high reactivity coke by close placement between iron-ore and carbon (i.e. by using carbon composite iron-ore and coke and ore mixture in packed bed).2) The final reduction degree of iron-ore with iron-ore rise by high reactivity coke or iron-ore and close placement between iron-ore and carbon and the high temperature gas flow resistance decreased3) The shrinkage resistance at high temperature decreased by using a carbon composite, and increased by using mixture of coke and ore.